Fractionation of the copper, oxygen and hydrogen isotopes between malachite and aqueous phase. (1st May 2021) - Plumhoff, Alexandra M.; Mathur, Ryan; Milovský, Rastislav; Majzlan, Juraj
Abstract: Studies of the equilibrium isotope properties of stable isotopes of minerals have been initiated principally because of their application to the solution of geochemical problems. Therefore, we examined malachite, a common secondary mineral in the oxidation zone of ore deposits. Stable isotope characterization can contribute needed information on the formation of malachite by establishing the isotopic composition of the parental waters. The equilibrium oxygen and hydrogen isotope fractionations between malachite and solution were determined by precipitation experiments over the temperature range from 10 to 65 °C and could be distinguished in two sets of fractionation factors depending on the temperature. For 45–65 °C, the fractionation is expressed as 1000 ln α mal - sol oxygen = 2.87 ( 10 6 / T 2 ) + 0.96 and 1000 ln α mal - sol hydrogen = - 1.47 ( 10 6 / T 2 ) - 22.3 with temperature ( T ) in Kelvin. With the application of the fractionation factors of oxygen and hydrogen of malachite onto source water from the meteoric water line, we were able to calculate the "malachite line" which represents the isotopic compositions of malachite that would precipitate from such water. We also examined the copper isotope fractionation factors between solution and malachite from 10 to 65 °C: 1000 ln α sol - mal copper = 0.033 ( 10 6 / T 2 ) - 0.19 with fractionation shift of Δ 65 Cu malachite - solution = - 0.17 ± 0.05 ‰. This fractionation shift implies that chemical reactions without change of the redox state yield only minor copper isotope fractionation. The calculated fractionation factors of oxygen and hydrogen were used to determine the oxygen and hydrogen isotopic composition of the parental waters of natural malachite samples from a number of localities worldwide. With δ 18 O VSMOW values of +22.1 to +29.5 ‰ and δ D values of - 132 to - 61 ‰ for the natural malachite and δ 18 O VSMOW values of - 14.5 to - 7 ‰ and δ D values of - 107 to - 36 ‰ for the parental water together with the Cu isotopes, it is to assume that all investigated malachite samples are supergene samples which formed from meteoric water. Even in massive malachite samples from Ural Mts. (Russia), no signs of other fluids were detected from the isotopic composition.